Pembelajaran Steam Dan Perkembangan Kognitif Anak Usia Dini - Wonis Mailan; Dinda Snae; Venia Fangidae; Febriyanti Bifel; Vebi Frare; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Cognitive development is a crucial aspect in demonstrating thinking skills, problem-solving skills, and early childhood learning readiness. The purpose of this study was to determine the effect of STEAM learning on the cognitive development of children aged 4-6 years. The research method was quantitative. The sampling technique used purposive sampling, specifically children aged 4-6 years. The respondents were 10 children aged 4-6 years at Grace Sikumana Early Childhood Education (PAUD) in Kupang City. Data collection used a questionnaire with instruments in the form of a STEAM learning scale and cognitive development. The STEAM learning scale was developed by Yakman (2008) and is called the STEAM Education Framework. The cognitive development scale was developed by Jean Piaget (1964) and is called the Cognitive Development Scale. The data analysis technique used simple linear regression. The findings revealed a positive and significant effect of STEAM learning on the cognitive development of children aged 4-6 years, amounting to 1.7%. This means that better STEAM learning can improve early childhood cognitive development. This shows that the more optimal the implementation of STEAM learning, the better the cognitive development of early childhood. Therefore, teachers are expected to implement STEAM learning creatively and in an integrated manner to support optimal cognitive development in children.